2020
DOI: 10.3762/bjoc.16.80
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new asparagine-based glycopeptides for future scanning tunneling microscopy investigations

Abstract: For investigations on the biological functions of oligosaccharides and peptidomimetics, new asparagine-based mono- and disaccharides containing glycopeptides were prepared in solution. The applicability of two common peptide coupling reagents, using an orthogonal Fmoc/t-Bu strategy along with acetyl protecting groups for the carbohydrate moiety, was studied. Thus, the prepared libraries of glycopeptides were designed as model systems of cell surfaces for future investigations by combined preparative mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The respective fully acetylated glycosylamines 2a–f have been synthesized from the corresponding azides 1a–f by catalytic hydrogenation according to literature‐known procedures and were immediately used without further purification in the next step (Scheme 2). 36 Acetyl groups have been exclusively used for protecting the hydroxyl functions in precursors 1a–f and 2a–f because it has been previously shown that acetyl protecting groups are ideally suited for peptide syntheses using the Fmoc/O t Bu strategy and because they are stable under the conditions of HBTU‐promoted condensations 36 . Furthermore, acetyl groups can be removed under mild conditions in the final deprotection step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The respective fully acetylated glycosylamines 2a–f have been synthesized from the corresponding azides 1a–f by catalytic hydrogenation according to literature‐known procedures and were immediately used without further purification in the next step (Scheme 2). 36 Acetyl groups have been exclusively used for protecting the hydroxyl functions in precursors 1a–f and 2a–f because it has been previously shown that acetyl protecting groups are ideally suited for peptide syntheses using the Fmoc/O t Bu strategy and because they are stable under the conditions of HBTU‐promoted condensations 36 . Furthermore, acetyl groups can be removed under mild conditions in the final deprotection step.…”
Section: Resultsmentioning
confidence: 99%
“…However, this reaction protocol can likewise be used for other natural or unnatural amino acids, which our laboratory could show earlier 34–36 …”
Section: Introductionmentioning
confidence: 95%
“…We first highlight the capabilities of STM imaging and DFT modeling in characterizing monosaccharide structures of glycans. We imaged two glycopeptides ( 26 ) (Fig. 1, B and C) composed of a disaccharide (cellobiose, Glcβ1–4Glc, or lactose, Galβ1–4Glc) linked to a tripeptide, and three glycosaminoglycans (GAGs) (Fig.…”
Section: Direct Imaging Of Glycoconjugates Soft-landed At a Surfacementioning
confidence: 99%